Nivel de incertidumbre e interrelación entre el profesional de enfermería y el cuidador familiar del paciente intervenido quirúrgicamente - Malca Palacios, Mirtha Natalia (2023)
This descriptive, quantitative, correlational and cross-sectional investigation was carried out with the objective of determining the association between the level of uncertainty and the interrelationship with the nursing professional of the family caregiver of the patient who underwent surgery at EsSalud Cajamarca Hospital II. The sample consisted of 67 family caregivers to whom two validated questionnaires were applied: one to measure the level of uncertainty (PPUS-FM) and another to measure the nurse-family caregiver relationship. Statistical analysis was done using SPSS Version 28 software, using Fisher's exact test and Kendall's correlation coefficient to determine the relationship between the variables. The results show that the relationship level of between the nursing professional and the family caregiver was 43,3% high, 34,3% medium, and 22,4% low. The level of uncertainty of the family caregiver was 68,7% low, 25,3% intermediate and 6% high. The statistical analysis shows a highly significant inverse association between variables (p < 0.005), concluding that there is a clear association between the level of uncertainty and the relationship between the nursing staff and the family caregiver. It is recommended to keep implementing strategies to improve the communication and interpersonal relationship of the nursing staff with the family caregiver to further reduce uncertainty in the family environment of the surgical patient